Chapter Raccolte librarie e archivi di persona alla Biblioteca di scienze sociali dell'Università di Firenze: stato dell'arte - Cestone, Giovanna (Strumenti per la didattica e la ricerca, 2021)
The text examines the mission of an academic library in order to develop its collections and services, but also to preserve and enhance the archives, donated by professors or associations.